Resistensi Politik Masyarakat Di Desa Adat Intaran Provinsi Bali Terhadap Proyek LNG Sidakarya - Mahmuda, Diana; Wisesa, Rafif Aryatha; Maulidito, Ardhivan Haikal (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
The state of Indonesia as a country that upholds democratic values provides space for local communities to express an attitude toward the existence of economic and political interests towards the government and corporations in the form of resistance on behalf of the interests of the affected communities. In general, the discussion on the emergence of resistance in local communities was born due to a conflict of interest. One of the resistance issues currently being discussed in Indonesia is the rejection of the construction site for the Sidakarya Bali LNG Project by the Intaran Traditional Village. The conflict occurred due to the transfer of the construction site from Benoa Harbor to the Sanur area near the Tahura Ngurah Rai mangrove area (part of the Intaran Traditional Village) which was originally intended as a protected area. The focus of the author in this study is an effort to review the factors causing the rejection and resistance carried out by the Intaran Bali Traditional Village, the form of resistance carried out, who the main actors involved, the problems of differences in interests that occur, and the discussion of political economy through the policies of the Bali Provincial government. . This study uses descriptive qualitative research methods using data collection through interviews and literature study. The results of this study indicate that the LNG Project so far has not been ascertained whether the policy is considered elitist or not because the final decision of the Bali Provincial Government on the location of the LNG Project development has not been inaugurated.